Initial Stages of ZrB2–30 vol% SiC Oxidation at 1500°C. Issue 5 (31st January 2014) - Shugart, Kathleen; Jennings, Wayne; Opila, Elizabeth; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> The initial oxidation behavior of ZrB2–30 vol% SiC was analyzed with the goal of understanding any relationship to the variable oxidation performance observed at longer times. A box furnace was used to oxidize samples for times as short as 10 s and up to 100 min at 1500°C in air. The samples were characterized using mass change, scanning electron microscopy, energy dispersive spectroscopy, X‐ray diffraction, and X‐ray photoelectron spectroscopy to explore the oxidation behavior. The presence of borosilicate glass and ZrO2 was observed on the surface at times as early as 10 s. Bubble formation in the borosilicate glass was observed after 30 s of oxidation and is attributed to uneven distribution of the glass. The impact of surface roughness on oxidation was also explored and found to be negligible for times greater than 30 s.